Synthesis of het(aryl) imidazole C-nucleoside analogues by CoFe2O4 NPs catalyzed muti-component coupling reaction. (15th May 2019) - Zhang, Fuyi; Li, Yang; Gao, Fei; liu, Hong; Zhao, Yufen
Abstract: A general synthesis of hetaryl and aryl C-4(5) linked imidazole C -nucleoside analogues has been developed by the reaction of sugar alkynes with het(aryl) iodides, KMnO4 /TBAB oxidation and CoFe2 O4 NPs catalyzed muti-component coupling of the corresponding diketones, NH4 OAc and aromatic aldehydes in one-pot. The sugar alkynes include pyranosides and furanosides with acid sensitive protecting groups. The het(aryl) iodides comprise iodoaromatics, iodoheterocycles, and sterically hindered iodoheteroaromatics. Graphical abstract: Image 1 Highlights: A series of novel het(aryl) imidazole C-nucleoside analogues have been synthesized by muti-component coupling in one-pot. The synthetic method has broad substrate scope and good compatibility with fuction groups. The CoFe2 O4 NPs catalyst for this coupling is cheap, readily separated by an external magnetic field and can be reused. The muti-component coupling reaction is tolerant of various pyranosides and furanosides having sensitive groups, and sterically bulky substituents.